Kajian Pustaka Pengembangan Media Pembelajaran Edukatif Dan Interaktif Di Jenjang Sekolah Dasar - Hanik Rahmawati Solikhah (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2025)
Islamic Religious Education (PAI) learning in elementary schools faces challenges in student engagement and motivation due to the dominance of conventional methods. This study aims to describe the urgency, concept, and strategy for developing educational and interactive technology-based learning media to improve the effectiveness of PAI learning. Educational media are tools that not only deliver material but also shape students' character. Interactive media provides space for active participation and feedback that strengthens understanding. Ideal media development refers to behavioral, cognitive, and constructivist learning theories and instructional design models such as ADDIE. The integration of technology through learning videos, digital quizzes, and augmented reality plays a significant role in creating enjoyable and meaningful learning experiences. This study emphasizes the importance of designing contextual, communicative media appropriate to elementary school students' characteristics to support the success of Islamic character education in the digital era.